A snakebite caused by a bushmaster (Lachesis muta): report of a confirmed case in State of Pernambuco, Brazil - Lima,Pedro Henrique Santana de (2015)
ABSTRACTWe report a case of envenomation caused by a bushmaster ( Lachesis muta) in a male child in State of Pernambuco, Brazil. The victim showed discrete local manifestations, but presented altered blood coagulation 2 hours after the bite. Ten ampoules of bothropic-lachetic antivenom therapy were administered, and 48 hours later, the patient showed discrete edema, pain, and ecchymosis around the bite and normal blood coagulation. The patient was discharged 5 days after the envenomation. The prompt administration of specific treatment was important for the favorable outcomes observed.